Basal ganglia calcifications is not inconsequential in pediatric cases - Erok, Berrin; Tatar, Sertaç; Uzunhan, Tuğçe Aksu; Bezen, Diğdem; Önder, Hakan (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Basal ganglia calcification (BGC) in pediatric population is rare and is considered as a pathological finding. Various causes may be responsible for BGC including hypoparathyroidism, various infectious, toxicities or hereditary disorders. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. We aimed to present a 8 year old boy presented with generalized seizure and bilateral small amount of globus pallidum calcifications on neuroimaging studies leading to the diagnosis of idiopathic hypoparathyroidism, which is a treatable cause of seizure. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 8-year-old boy presented to our emergency department with generalized seizure for the first time in his life. There was no history of previous head trauma and his family history was unremarkable. Neurological examination revealed no pathological findings. Radiological imaging studies revealed only bilateral small amount of globus pallidus calcifications. He was referred to the pediatric endocrinology department for further evaluation of the hypocalcemic convulsion, where laboratory investigations revealed idiopathic hypoparathyroidism as the cause of hypocalcemic convulsion with exclusion of the other causes. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Even a small amount of BGC in pediatric patients may be the sign of primary hypoparathyroidism and should be evaluated with serum electrolyte levels for early diagnosis and for the prevention of multisystemic complications of hypoparathyroidism.